Bioabsorbable Bypass Grafts Biofunctionalised with RGD Have Enhanced Biophysical Properties and Endothelialisation Tested In vivo - Antonova, Larisa V.; Seifalian, Alexander M.; Kutikhin, Anton G.; Sevostyanova, Victoria V.; Krivkina, Evgeniya O.; Mironov, Andrey V.; Burago, Andrey Y.; Velikanova, Elena A.; Matveeva, Vera G.; Glushkova, Tatiana V.; Sergeeva, Evgeniya A.; Vasyukov, Georgiy Y.; et al. (Frontiers in Pharmacology, 2016)
Small diameter arterial bypass grafts are considered as unmet clinical need since the current grafts have poor patency of 25% within 5 years. We have developed a 3D scaffold manufactured from natural and synthetic biodegradable polymers, poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and poly(𝜀-caprolactone) (PCL), respectively. Further to improve the biophysical properties as well as endothelialisation, the grafts were covalently conjugated with arginine-glycine-aspartic acid (RGD) bioactive peptides. The biophysical properties as well as endothelialisation of PHBV/PCL and PCL 2 mm diameter bypass grafts were assessed with and without biofunctionalisation with RGD peptides in vitro and in vivo. Morphology of the grafts was assessed by scanning electron microscopy, whereas physico-mechanical properties were evaluated using a physiological circulating system equipped with a state of art ultrasound vascular wall tracking system. Endothelialisation of the grafts in vitro and in vivo were assessed using a cell viability assay and rat abdominal aorta replacement model, respectively. The biofunctionalisation with RGD bioactive peptides decreased mean fiber diameter and mean pore area in PHBV/PCL grafts; however, this was not the case for PCL grafts. Both PHBV/PCL and PCL grafts with RGD peptides had lower durability compared to those without; these durability values were similar to those of internal mammary artery. Modification of PHBV/PCL and PCL grafts with RGD peptides increased endothelial cell viability in vitro by a factor of eight and enhanced the formation of an endothelial cell monolayer in vivo 1 month postimplantation. In conclusion, PHBV/PCL small-caliber graft can be a suitable 3D scaffold for the development of a tissue engineering arterial bypass graft.